Megarthrus of southern India and Sri Lanka, with notes on their phylogenetic and biogeographical relationships (Coleoptera: Staphylinidae: Proteininae) - Cuccodoro, Giulio; Liu, Zhiping (Zootaxa, 2016)
South of the Deccan Plateau the genus Megarthrus Curtis was represented so far in the Indian subcontinent only by M. rufomarginatus Cameron, of the hilly areas of Tamil Nadu and Kerala, and Megarthrus bimaculatus Fauvel, of Sri Lanka. Here we describe three additional species from this area: M. nilgiriensis sp. n. and M. narendrani sp. n., both from southern India and strongly resembling M. bimaculatus, and M. lanka sp. n., of Sri Lanka and strongly resembling M. rufomarginatus. The five species of Megarthrus occurring in southern India and Sri Lanka are keyed and illustrated with colour pictures of habitus, genitalia and other main diagnostic characters. They belong to two homogeneous complexes of species—the «bimaculatus-complex» and the «rufomarginatus-complex»—that uniquely share many important features with the Sumatran M. sumatrensis Cameron and the Philippine M. vastus Wendeler, with which they constitute the here defined «vastus-group» of species. The Megarthrus fauna of southern India and Sri Lanka appears thus not only disjunct and completely distinct from that phylogenetically and taxonomically much more diverse of North of the Indo-Gangetic Plain, but also directly related to that of the Sunda shelf.